2004
DOI: 10.1021/jp047193n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Pt Particle Adsorbate Bonding:  Influence of Support Ionicity and Implications for Catalysis

Abstract: The influence of the support ionicity on the adsorption of H, CH x (x ) 2, 3), and O on supported Pt particles is investigated using density functional theory (DFT). The DFT calculations reveal that the importance of the 6s,p states for the Pt adsorbate bonding increases in the order Pt-O < Pt-CH 2 < Pt-CH 3 < Pt-H. Both the Pt-H and Pt-O bond strengths are strongly affected by changes in the support ionicity whereas the difference for the Pt-CH x bond strength is much smaller. The Pt-H bond strength is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 50 publications
11
52
1
Order By: Relevance
“…The hydrogen chemisorption capacity of Pt is directly influenced by the ionicity of the support oxygen. The H/M results presented in this paper are completely in line with previously published Pt AXAFS, XANES, XPS, and CO FTIR data [7,8,23] and provide an experimental proof of our recently published DFT calculations [22]. They confirm the interatomic potential model [17] that we have proposed as a basis for metal-support interaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The hydrogen chemisorption capacity of Pt is directly influenced by the ionicity of the support oxygen. The H/M results presented in this paper are completely in line with previously published Pt AXAFS, XANES, XPS, and CO FTIR data [7,8,23] and provide an experimental proof of our recently published DFT calculations [22]. They confirm the interatomic potential model [17] that we have proposed as a basis for metal-support interaction.…”
Section: Discussionsupporting
confidence: 91%
“…The H/Pt s data presented in Table 4 show that the number of hydrogen atoms chemisorbed per surface Pt is highest for Pt particles on the most ionic (basic) support (NaY) and lowest for Pt particles on the most covalent (acidic) support (H-USY). This implies that the H/M data presented in this paper are a direct experimental proof of recently published DFT calculations [22]. Moreover, they are completely in line with previously published Pt EXAFS, XANES, XPS, and CO FTIR [7,8,19,23] data and confirm our interatomic potential model that was put forward as a basis for metal-support interaction [17].…”
Section: Influence Of Ionicity Of the Support On The Hydrogen Chemisosupporting
confidence: 92%
See 2 more Smart Citations
“…[10] The complete density of states (DOS) of the Pt is shifted to higher binding energy, and the location of the 6s,p interstitial bonding orbital (IBO) moves from the surface to the metal-support interface of the Pt particles with decreasing ionicity of the support 1 (with decreasing electronic charge on the oxygen atoms of the support). [26] The variations in support oxygen charge density are often the result of promotion effects or alterations in the support cations (e.g., Si/Al ratio), and so these are next nearest neighbour effects. [8,15] The results mentioned above for bulk metal systems, organometallic systems, and supported metal catalysts have shown that AXAFS is a viable tool for probing the influence of the local surroundings on the electronic properties of a central atom.…”
Section: Introductionmentioning
confidence: 99%